2019
DOI: 10.1002/lary.28023
|View full text |Cite
|
Sign up to set email alerts
|

Single‐incision sural nerve harvest: Technical considerations for cross‐facial nerve grafting

Abstract: b.a. is the senior author and performed all of the procedures described, and conceptualized and edited the article. l.e.i. was responsible for data collection and analysis, editing the manuscript, and compiling the figures. d.b.y. performed the first single‐incision nerve harvest with b.a. and is responsible for b.a. adopting the practice. b.l. is b.a.’s partner and assisted with the majority of surgeries and proofread the manuscript. g.g.m. was cosurgeon on many of the described cases and is partly responsibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Certain researchers have suggested that small skin incisions must be made and a stripper device must be used to minimize the negative effects of traditional methods in the SN harvest. Although nerve harvesting with the stripper device is possible quickly and has significant advantages in reducing scarring, there is a possibility of injury to the SN and lesser saphenous vein, as the harvest is done blindly[19][20][21]. For this reason, endoscopy-guided nerve harvesting enables direct monitoring of the nerve and minimizes the risk of injury to other structures in the region.…”
mentioning
confidence: 99%
“…Certain researchers have suggested that small skin incisions must be made and a stripper device must be used to minimize the negative effects of traditional methods in the SN harvest. Although nerve harvesting with the stripper device is possible quickly and has significant advantages in reducing scarring, there is a possibility of injury to the SN and lesser saphenous vein, as the harvest is done blindly[19][20][21]. For this reason, endoscopy-guided nerve harvesting enables direct monitoring of the nerve and minimizes the risk of injury to other structures in the region.…”
mentioning
confidence: 99%